A comparison of satisfaction levels between domestic and international tourists with Newquay as a holiday destination - Blyth, Sarah (2008)
Satisfaction is a pertinent issue in the field of tourism, which has significant implications for managers and marketers of a destination. Many studies have been conducted on tourist satisfaction with international and domestic holiday destinations, but there is a relative lack of cross-cultural research in this area. The increasing numbers of tourists of widely differing cultures to a destination is heightening the pressure on destination managers to segment the market and cater for the different needs of each cultural group. This paper presents the findings of a satisfaction survey carried out among international and domestic tourists visiting Newquay during the peak summer season in 2008. The primary purpose of this study is to investigate whether cultural variations have a significant impact upon touristsÃ¢ÂÂ satisfaction levels, particularly regarding domestic and international tourists. Culture is defined by country of origin, and the affect of nationality on tourist satisfaction is also determined. The findings indicated that there were no significant differences between domestic and international tourists in their overall satisfaction levels with the same destination. However, significant differences were found between domestic tourists and those from New Zealand and Australia, emphasising the need to segment tourism markets based on nationality. The implications of the findings and the limitations of the study, and of comparative satisfaction research are discussed.